Strangers to the Law Gay People on Trial - Keen, Lisa (University of Michigan Press, 1998)
In 1992, the voters of Colorado passed a ballot initiative amending the state constitution to prevent the state or any local government from adopting any law or policy that protected a person with a homosexual, lesbian, or bisexual orientation from discrimination. This amendment was immediately challenged in the courts as a denial of equal protection of the laws under the United States Constitution. This litigation ultimately led to a landmark decision by the United States Supreme Court invalidating the Colorado ballot initiative. Suzanne Goldberg, an attorney involved in the case from the beginning on behalf of the Lambda Legal Defense and Education Fund, and Lisa Keen, a journalist who covered the initiative campaign and litigation, tell the story of this case, providing an inside view of this complex and important litigation.